The Effect of Supply Chain Indicators on the Business Performance of Food Industry in Indonesia - Benny Prakarsa Yustianto; Satria Bangsawan; Mahrinasari MS (International Journal of Supply Chain Management, 2020)
The performance is considered to be an important part of the business for their long term survival. For this purpose, the supply chain integration (SCI) indicators are considered to be an important part to increase the performance of the organization. The organizations which have a little attention on the SCI has low level of their performance. To address this issue, the current study purpose is to investigate the impact of supply chain indicators on the business performance (BP) of food industry. For this purpose, data has been collected from the 450 top and middle managers that were working in the food industry of Indonesia. The Structural Equation Modeling (SEM) of the study has shown that internal integration (INI) and external integration (EXI) have a positive and significant relationship with the BP. On the other hand, information technology integration (ITI) has insignificant relationship with the BP. While, supplier buyer relationship coordination integration (SBRCI) and logistics integration (LOI) have a positive and significant relationship with the BP. These findings indicate that food industry of Indonesia played an important role on the SCI to increase their BP. Therefore, this research is considered to be a pioneer study in which SCI played an important role to increase their BP. The research limitations and future direction were also discussed at the end of the study.